Do bond yields follow the hierarchy of risk post BRRD?. (29th July 2020) - Cucinelli, Doriana; Gai, Lorenzo; Ielasi, Federica
Abstract: With a sample of 4, 065 bonds issued by 63 banks from 12 euro area countries during 2013–2017, this study investigates how introducing bail‐in regulation has influenced bond yields in secondary markets, by distinguishing between non‐bail‐inable and different classes of bail‐inable bonds. The bail‐in risk premium does not follow the hierarchy of risk; it is stronger for less risky bonds. The effect on the spread between senior unsecured and non‐bail‐inable bonds is much higher than for subordinated bonds. Regarding subordinated bonds, the impact is higher for securities excluded from regulatory capital than for those included.